Dynamics in Education Politics - Simola, Hannu (Taylor & Francis, 2017)
In the field of comparative education without a strong theory-driven approach it is hard to go beyond merely listing the similarities and differences that make it possible to create countless rankings, but reveals little about specific and shared developmental processes between education systems. This book introduces a new theoretical framework characterised as Comparative Analytics of Dynamics in Education Politics (CADEP) as an ambitious response to this political, intellectual and scientific problem.